2016
DOI: 10.1097/opx.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Refraction, Peripheral Eye Length, and Retinal Shape in Myopia

Abstract: Effects of meridian and refraction on RPR and RPEL patterns are consistent with effects on retinal shape. Patterns derived from one of these predict the others: more positive (hyperopic) RPR predicts more negative RPEL and steeper retinas, more negative RPEL predicts more positive relative peripheral refraction and steeper retinas, and steeper retinas derived from peripheral eye lengths predict more positive RPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
66
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 29 publications
16
66
4
1
Order By: Relevance
“…For the horizontal field, emmetropes tend to have peripheral myopia, while myopes have reduced myopia in the periphery (termed relative peripheral hyperopia). For the vertical field, both emmetropes and myopes have relative peripheral myopia with our recent study indicating that this is less in myopes than in emmetropes [23]. Using the retinal shape derived from our previous study, our eye modelling predicted only a small part of the difference between the refractive patterns for the horizontal and vertical meridians (Table 2 [28]); as the meridional differences in this study were less than in the earlier work, changing the retinal shapes would give even less meridional effect on the peripheral optics modelling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the horizontal field, emmetropes tend to have peripheral myopia, while myopes have reduced myopia in the periphery (termed relative peripheral hyperopia). For the vertical field, both emmetropes and myopes have relative peripheral myopia with our recent study indicating that this is less in myopes than in emmetropes [23]. Using the retinal shape derived from our previous study, our eye modelling predicted only a small part of the difference between the refractive patterns for the horizontal and vertical meridians (Table 2 [28]); as the meridional differences in this study were less than in the earlier work, changing the retinal shapes would give even less meridional effect on the peripheral optics modelling.…”
Section: Discussionmentioning
confidence: 99%
“…The second is that there are asymmetries in the retina close to the fovea that cannot be picked up by fitting curves to more than 50% of the retina, or the scatter in the data over a small posterior region makes it difficult to recognize these differences. We note that our "partial coherence interferometry" method for estimating retinal shape by combining peripheral axial length measurements with symmetric ocular modelling found meridional differences, with retinas being steeper by about 1.5 mm vertex radius of curvature in the horizontal meridian than in the vertical meridian in an East Asian group, and with the shapes being strongly correlated with peripheral refraction (steeper retinas accompanying higher relative peripheral hyperopia) [23]. A further study with a combined East Asian/Caucasian group found a difference in vertex radius of curvature of 1.2 mm between meridians [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐six East Asian and 40 Caucasian young adult participants were recruited. Results of the East Asian participants have been reported in the context of comparing trends in relative peripheral refraction, relative peripheral eye length and retinal shape …”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies involving humans have investigated peripheral refraction, with only a few looking at peripheral refraction and retinal shape in combination. Verkicharla et al reported that peripheral refraction, peripheral eye lengths, and retinal shapes measured from partial coherence interferometry were significantly affected by race, as well as by meridian and refraction. East Asians were found to have steeper retinas and greater relative peripheral hyperopia than Caucasians, with steepness being greater along the horizontal meridian than the vertical meridian.…”
Section: Peripheral Defocusmentioning
confidence: 99%